Analysis of UMKM Product Quality Control Using the Statistical Quality Control (SQC) Method: Analisis Pengendalian Kualitas Produk UMKM dengan Metode Statistical Quality Control (SQC) - Ramadhani, Mughni Rizqi; Muh Widodo, Eko; Imron Rosyidi, Muhammad (Universitas Muhammadiyah Magelang, 2024)
UMKM Keripik Bariklana is one of the cassava-based food processing businesses established in 2015 and located in Sumurarum Village, Grabag District, Magelang Regency, Central Java. UMKM Keripik Bariklana produces one variant of cassava balado chips with an average production capacity of 1,500 kg of cassava chips per month which is worked on by 6 male workers and 4 female workers. However, UMKM Keripik Bariklana still faces problems in its production process, namely there are still defective products in the form of crushed chips and broken chips. The purpose of this study was to identify the factors that cause the emergence of defective products and provide suggestions for improvements aimed at achieving zero defect products of UMKM Keripik Bariklana. The method used in quality control to achieve zero product defects is using the Statistical Quality Control (SQC) method. After being analyzed with a fishbone diagram, the results of this study showed that the factors causing defective cassava chips are Material, Machine, Method and Man. Improvements made to achieve zero product defects are that before purchasing raw materials, the age of cassava must be checked until harvest time, weather factors, and the characteristics of cassava from each different region must be checked. Employees are given useful training to increase knowledge and develop skills in the cassava chips making process. Carefully adjust and check machine components before use in the production process, such as sharpening knives if the blade is blunt and replacing components if any are damaged. It is necessary to review the work method whether employees understand and understand the work method, for that it is necessary to design a more systematic one and use language that is easier to understand. So that the SOP that is made can be run properly and correctly